The effect of Neurofeedback SMR training on psycho-physiological and behavioral phenomena in professional handball players: An exploratory study - Lepir, Dusko; Lakić, Siniša; Martić, Tatjana; Soldat, Tamara; Zlojutro, Nemanja; Sekulić, Željko (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed on examining the effects of Sensory Motor Rhythm training (SMR-T) on various psychophysiological and behavioral phenomena in professional handball players. The study involved ten handball players, with no prior experience in neurofeedback training, four undergoing the SMR-T protocol and six serving as the control group. Using a small-N, multiple-measures design, changes in reaction time, focused attention, general and pre-competition anxiety were monitored, while interviews assessed the subjective experiences and perceptions of the protocol’s effects in the experimental group. Quantitative analysis based on descriptive parameters revealed a mild tendency towards improvement in pre-competition anxiety in the control group, while much stronger tendencies for improvement were observed in the experimental group across nearly all tested parameters, specifically regarding reaction time, focused attention, general anxiety, and pre-competition anxiety. Inferential statistics, likely due to the small sample size, did not confirm statistically significant differences between groups after the intervention, except for general and pre-competition anxiety. However, moderate to strong effect sizes suggest that this method may have significant potential for impacting the outcomes measured. Qualitative findings also point to psychological benefits of SMR-T, including perceived reduction in pre-competition anxiety, enhanced focused attention, improved sleep, and other positive behavioral effects. The results suggest that SMR-T could be a valuable tool, not only for performance enhancement, but also for improving overall well-being in professional athletes.